Enhanced production of erythritol by Yarrowia lipolytica on glycerol in repeated batch cultures. (1st January 2014) - Mirończuk, Aleksandra M; Furgała, Joanna; Rakicka, Magdalena; Rymowicz, Waldemar
Abstract: Erythritol is an important natural sweetener, industrially produced only by fermentation on glucose media. Glycerol is an important renewable feedstock as it is the major by-product of the biodiesel production process; here we present an alternative way to convert this low-cost substrate into value-added products, such as erythritol. Repeated batch cultures (RBC) were performed to improve the productivity of erythritol from pure and crude glycerol. An acetate negative mutant of Yarrowia lipolytica Wratislavia K1 was found to be applicable for the production of high amounts of erythritol in RBC. When 20 % of fresh replaced medium was added, the strain Wratislavia K1 was able to produce 220 g l −1 erythritol, which corresponded to a 0.43 g g −1 yield and a productivity of 0.54 g l −1 h −1 . Additionally, the activity of the culture remained stable for more than 1, 000 h, i.e., 11 cycles of the repeated batch bioreactors.